Bioequivalence of Two Lamivudine Tablet Formulations - Santos-Magalhães, Nereide S.; Pontes, Adriana; Cavalcante, Renata M.; Costa, Roseane M. R.; Rangel, Frederico A.; Guimarães, M. Isabel V.; Carvalho, J. N. Leôncio de; de Souza, Samuel D. F.; de Oliveira, Hélio M.; Esteves, Isac L. C.; Ramalho, Mario S.; Vieira, Sandra L. A.; Alves, Antonio J. (Arzneimittelforschung, 2001)
The present study describes the determination of the bioavailability of a new commercial tablet formulation of lamivudine (CAS 134678-17-4) compared with a reference formulation. The comparative bioequivalence of the test and a reference formulation (each 3 × 150 mg) was assessed in 24 healthy volunteers by means of a randomized two-way crossover design. Prior to the study both the test and reference formulations were examined for conformation to chromato-graphic purity and drug content. Each volunteer received the test (T) and the reference formulation (R) with a one-week drug-free interval between administrations. The plasma concentrations of T were monitored over a period of 12 h after drug administration using a sensitive HPLC method. Pharmacokinetic parameters for T were determined from plasma concentration time data. Statistical tests were carried out at 90 % confidence intervals using a parametric method (three way ANOVA) for AUC and Cmax, and non parametric method for Tmax. The present study showed that both formulations were bioequivalent for the geometric mean of AUC(0–12), AUC(0-∞), Cmax, and Tmax at the 90 % confidence in terval. The bioavailability of the test (%) was 96.7, 93.3, 99.7, 100.3, respectively. The T : R ratio was, in each case, well within the acceptable range of 100 ±20 %.
Keywords: CAS 134678-17-4; Lamivudine, bioequivalence studies